Measurement of the top quark mass in the all- jets final state at root s=13 TeV and combination with the lepton plus jets channel - KAYA, MİTHAT (SPRINGER, 2019)
A top quark mass measurement is performed using 35.9 fb - 1 of LHC proton- proton collision data collected with the CMS detector at v s = 13 TeV. The measurement uses the tt all- jets final state. A kinematic fit is performed to reconstruct the decay of the tt system and suppress themultijet background. Using the ideogram method, the top quark mass ( mt) is determined, simultaneously constraining an additional jet energy scale factor ( JSF). The resulting value of mt = 172.34 +/- 0.20 ( stat+ JSF) +/- 0.70 ( syst) GeV is in good agreement with previous measurements. In addition, a combined measurement that uses the tt lepton+ jets and all- jets final states is presented, using the same mass extraction method, and provides an mt measurement of 172.26 +/- 0.07 ( stat+ JSF) +/- 0.61 ( syst) GeV. This is the first combined mt extraction from the lepton+ jets and all- jets channels through a single likelihood function.